Analisis dan Perancangan Sistem Informasi Penjualan Hijab Berbasis Web - Arsy Febrina Dewi, Lusi Mutia Lukman (LPPM-UNIKI, 2021)
Hijab is one of the important components for Muslim women who are used to cover the genitals. The development ofvarious hijab models is currently a separate trend among women. This has resulted in many shops selling hijab, one ofwhich is ByLilu Hijab Store in the city of Lhokseumawe. The increase in the number of stores requires entrepreneurs toinnovate in increasing sales. Sales data processing and stock checking at the Bylilu Hijab Store are still done manually,all data is recorded in the sales book. Incoming messages/chats from consumers are also a bit constrained because theadmin does not immediately reply to messages. By utilizing information technology that is currently growing, ByLiluHijab Store is trying to improve services by creating a sales information system. This system is designed web-based usingthe PHP programming language and My-SQL database. The system is designed so that it can be accessed by store adminsand consumers everywhere. it is easier for store admins to recap sales data and check product stock. In addition, thissystem also makes it easier for consumers to order hijab, and increase sales results at the ByLilu Hijab Store.